The relationship between open spaces and house prices in selected townships in Kuala Lumpur, Malaysia - Asmawi, M. Zainora; Hj. Mohd. Noor, Norzailawati; Manzahari, Mohd Nasrul Hanis; Abdullah, Alias (2014)
Nowadays, there is a particular concern on the urgent need for open spaces within the urban fabric as it provides significant services to the environmental quality of the areas. The research problem addresses the issue of the loss of open spaces to give way to other developments is obviously occurred in Kuala Lumpur, Malaysia. In relation to the economic growth of the nation, it is considerably noticeable that currently there is an increasing trend in the Malaysian housing price. However, there are not many studies undertaken to investigate the relationship between the provision of open spaces and house prices in the Malaysian context. As such, this research attempts to study and examine the relationship between open spaces and house prices in the selected townships in Kuala Lumpur. The aim of this research is to study the relationship between open spaces and house prices in Kuala Lumpur. This leads to the objectives which are: (1) to determine the elements of open spaces which influence the house prices; and (2) to determine the key micro factors involved in purchasing a house in selected townships in Kuala Lumpur. Three methods were employed namely: (1) literature reviews; (2) structured close-ended questions in questionnaires survey; and (3) site observation. The selected townships are Bandar Baru Bangi, Taman Melawati, Subang Jaya and Shah Alam with a total respondent of 200. The reliability test was conducted and the results of Cronbach‟s alpha value for green areas and its independent variables were 0.895 and considered acceptable, allowing the research to retain all variables for the analysis. The basic criterion for the respondent refers to the house owners only to justify the validity of the feedback on the questions posed to them. Information on house showed that the majority, 35.5% and 22% of them had owned the house between 6-10 years and 11-15 years respectively. A total of 43.5% of the respondents opted for the transacted price for the houses range between RM201,000-RM300,000. Whilst, the majority (24.5%) informed that the offered price would be between RM501,000-RM600,000. Respondents were asked on their perception of the importance of open spaces in relation to determine the offered housing price within their townships. Of several elements of open space, the results showed that the respondents regarded cleanliness as the most important one; this is followed by regular maintenance, facilities provided for the users and the strategic location of open space. The respondents selected the aspect of proximity of open space as the sixth place. In relation to the micro factors influencing house prices, a set of nine factors were determined and posed to the respondents to get their perception. The key micro factor was high quality construction materials and followed by the provision of adequate infrastructure and public facilities. The aspect of proximity of adequate open spaces was selected as the sixth place out of nine micro factors. The finding suggested that the relationship between open space and house price in the selected township does establish in a positive pattern, however, it was not considered as a strong relationship. The results show that the local context with different culture, attitude and level of awareness on the importance of greeneries produced a weak relationship between open space and house price. As a conclusion, this research has met its two outlined objectives, proven that there is a weak positive relationship established between the provision of open spaces and house price in the context of Malaysian housing market.